Combined spectroscopic and TDDFT study of single-double anthocyanins for application in dye-sensitized solar cells. (15th June 2018) - Prima, E. C.; Nuruddin, A.; Yuliarto, B.; Kawamura, G.; Matsuda, A.
Abstract : This research investigates single-double anthocyanins experimentally and theoretically for the first time. Abstract : This research investigates single-double anthocyanins experimentally and theoretically for the first time. The natural donor contribution of methoxyl and glucose groups on anthocyanin dyes from cyanidin-3-glucoside (C3G) and peonidin-3-glucoside (P3G) was studied for dye-sensitized solar cell application. Single (C3G, P3G) and double (C3G + P3G) dyes were characterized by UV-vis absorption spectroscopy, cyclic voltammetry, Fourier transform infrared, electrochemical impedance spectroscopy, including the theoretical and experimental photochemical properties for final dye-sensitized solar cell (DSSC) applications. All of the studied dyes show electron transfer and photo-energy conversion activities, with efficiencies up to 2.01% for the combined C3G + P3G dye. The spectroscopy method combined with the computational analysis is applied in order to provide a better understanding of how the dye combination stabilizes the electronic structure, the electrons on the C3G and P3G orbitals contribute to the joining electron transfer, and to improving the performance of the anthocyanin-based DSSC.